Genome-Wide Analysis of the DUF4228 Family in Soybean and Functional Identification of GmDUF4228–70 in Response to Drought and Salt Stresses - Leng, Zhi-Xin; Liu, Ying; Chen, Zhan-Yu; Guo, Jun; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Xu, Zhao-Shi; Cui, Xi-Yan (Frontiers in Plant Science, 2021)
Domain of unknown function 4228 (DUF4228) proteins are a class of proteins widely found in plants, playing an important role in response to abiotic stresses. However, studies on the DUF4228 family in soybean (Glycine max L.) are sparse. In this study, we identified a total of 81 DUF4228 genes in soybean genome, named systematically based on their chromosome distributions. Results showed that these genes were unevenly distributed on the 20 chromosomes of soybean. The predicted soybean DUF4228 proteins were identified in three groups (Groups I–III) based on a maximum likelihood phylogenetic tree. Genetic structure analysis showed that most of the GmDUF4228 genes contained no introns. Expression profiling showed that GmDUF4228 genes were widely expressed in different organs and tissues in soybean. RNA-seq data were used to characterize the expression profiles of GmDUF4228 genes under the treatments of drought and salt stresses, with nine genes showing significant up-regulation under both drought and salt stress further functionally verified by promoter (cis-acting elements) analysis and quantitative real-time PCR (qRT-PCR). Due to its upregulation under drought and salt stresses based on both RNA-seq and qRT-PCR analyses, GmDUF4228-70 was selected for further functional analysis in transgenic plants. Under drought stress, the degree of leaf curling and wilting of the GmDUF4228-70-overexpressing (GmDUF4228-70-OE) line was lower than that of the empty vector (EV) line. GmDUF4228-70-OE lines also showed increased proline content, relative water content (RWC), and chlorophyll content, and decreased contents of malondialdehyde (MDA), H2O2, and O2–. Under salt stress, the changes in phenotypic and physiological indicators of transgenic plants were the same as those under drought stress. In addition, overexpression of the GmDUF4228-70 gene promoted the expression of marker genes under both drought and salt stresses. Taken together, the results indicated that GmDUF4228 genes play important roles in response to abiotic stresses in soybean.